Anode for secondary battery, slurry for anode, and method for producing anode
The combination of flaked natural graphite and silicon-based materials in the negative electrode of lithium-ion batteries addresses the conductivity issues, ensuring stable charging and discharging cycles with enhanced capacity retention.
Patent Information
- Application Number
- JP2020216840
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-25
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2040-12-25
AI Technical Summary
Existing secondary batteries, particularly lithium-ion batteries, face challenges in maintaining a conductive path between carbon-based and silicon-based materials, leading to capacity underutilization and capacity deterioration due to expansion and contraction during charging and discharging, with issues in dispersing nanocarbon materials and high costs.
A negative electrode comprising a mixture of artificial and natural graphite with partially flaked natural graphite to form exfoliated portions, combined with silicon-based materials, and a conductive material like carbon black, to establish a highly conductive path.
The solution ensures stable charging and discharging cycles with improved life characteristics by maintaining conductivity and preventing isolation of silicon-based particles, enhancing the overall capacity retention rate.
Smart Images

Figure 0007603443000002 
Figure 0007603443000003 
Figure 0007603443000001
Abstract
Description
Technical Field
[0001] The present invention relates to a negative electrode for a secondary battery, a slurry for a negative electrode, and a method for manufacturing a negative electrode.
Background Art
[0002] As technology development and demand for mobile devices and electric vehicles increase, the demand for secondary batteries as an energy source is rapidly increasing. Among such secondary batteries, lithium-ion secondary batteries having a high energy density, a high voltage, a long cycle life, and a low self-discharge rate have been put into practical use and widely used. Currently, research is being actively conducted to increase the capacity of such lithium-ion secondary batteries.
[0003] Silicon-based materials such as silicon oxide and silicon-based alloys have a larger theoretical capacity density than carbon-based materials such as graphite, which is currently the mainstream. Therefore, they are expected as negative electrode materials for improving the energy density of lithium-ion secondary batteries and have been conventionally studied. Among silicon-based materials, silicon oxide (SiO x (0 < x < 2), for example, SiO) has a relatively low expansion rate and has been partially put into practical use. However, its initial efficiency is 20% or more lower than that of graphite, and when used alone, the difference in irreversible capacity from the positive electrode becomes large. Therefore, it is currently used by mixing with a carbon-based material by about several percent. Silicon-based alloys having a lower irreversible capacity than silicon oxide have problems with expansion rate, and it is also being considered to mix with graphite to relax the expansion rate of the entire electrode.
[0004] However, since carbon-based materials and silicon-based materials have different powder characteristics, conductivity, expansion rate, etc., when using a mixture of carbon-based materials and silicon-based materials, it is difficult to form a structure in which the entire active material is utilized while maintaining the conduction path between the carbon-based material and the silicon-based material during expansion and contraction due to repeated charge and discharge. Not only silicon-based materials with a large expansion rate, but also the capacity of carbon-based materials is gradually not utilized.
[0005] Furthermore, when artificial graphite is used as the carbon-based material, it has the advantage of having a lower expansion coefficient than natural graphite, but since it is hard, it is difficult to deform even by rolling, and voids are likely to form between the artificial graphite and the silicon-based material during the electrode production process, and small particles of the silicon-based material tend to become isolated, which leads to a decrease in initial capacity and capacity degradation during charging and discharging.
[0006] In order to ensure a conductive path in the negative electrode containing both a carbon-based material and a silicon-based material, it has been proposed to combine a silicon-based material, which is basically non-conductive, with a conductive carbon-based material (see, for example, Patent Document 1 and Patent Document 2), or to add a nanocarbon material such as graphene or carbon nanotube as a conductive material (see, for example, Patent Document 3). However, in the former case, there is a problem that it is difficult to ensure a conductive path between particles, and in the latter case, there are problems that it is difficult to uniformly disperse the nanocarbon material throughout the negative electrode, and the cost of the nanocarbon material is very high. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2019-067579 A [Patent Document 2] International Publication No. 2012 / 140790 [Patent Document 3] JP 2020-013718 A Summary of the Invention [Problem to be solved by the invention]
[0008] In view of the above-mentioned problems of the conventional art, the problem to be solved by the present invention is to provide a negative electrode for a secondary battery, a slurry for the negative electrode, and a method for producing the negative electrode, which can improve the life characteristics by establishing a highly and strongly conductive path in the negative electrode and enabling stable repeated charging and discharging. [Means for solving the problem]
[0009] According to one aspect of the present invention, there is provided a negative electrode for a secondary battery, the negative electrode comprising at least a graphite-based material and a silicon-based material as negative electrode active materials, and a conductive material, the graphite-based material comprising granules of artificial graphite and natural graphite, at least a portion of the natural graphite in the granules being partially flaked to form an flaked portion, the flaked portion being in contact with the silicon-based material or other granules of artificial graphite and natural graphite, or being composited with the silicon-based material.
[0010] In the negative electrode of the above embodiment, the silicon-based material may include one or both of silicon oxide and a silicon-based alloy.
[0011] In the negative electrode of the above embodiment, the silicon-based alloy may contain one or more of titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), and copper (Cu).
[0012] In the negative electrode of the above embodiment, the conductive material may be carbon black.
[0013] In the negative electrode of the above embodiment, the weight ratio of the graphite-based material to the silicon-based material may be 98:2 to 50:50.
[0014] In the negative electrode of the above embodiment, the weight ratio of the artificial graphite to the natural graphite in the granules may be 60:40 to 90:10.
[0015] There is also provided a secondary battery including the negative electrode of the above embodiment, the secondary battery further including a positive electrode, a separator interposed between the negative electrode and the positive electrode, and an electrolyte.
[0016] According to another aspect of the present invention, there is provided a slurry for a negative electrode of a secondary battery, the slurry for a negative electrode comprising a graphite-based material and a silicon-based material as negative electrode active materials, a conductive material, a solvent, and at least one of a thickener and a binder, such that the solid content in the slurry is 60% by weight or more, and the graphite-based material comprises granules of artificial graphite and natural graphite.
[0017] In the negative electrode slurry of the above embodiment, at least a part of the natural graphite in the granules can be partially exfoliated to form an exfoliated portion.
[0018] In the negative electrode slurry of the above embodiment, the solid content in the slurry can be 65% by weight or more and 75% by weight or less.
[0019] According to yet another aspect of the present invention, there is provided a method for producing a negative electrode for a secondary battery, the method including the steps of mixing a graphite-based material and a silicon-based material as negative electrode active materials, a conductive material, a solvent, and at least one of a thickener and a binder to prepare a slurry having a solid content of 60% by weight or more, kneading the slurry, and applying the slurry to a current collector to produce a negative electrode, wherein the graphite-based material is a granule of artificial graphite and natural graphite.
[0020] In the method of the above aspect, in the step of kneading the slurry, at least a portion of the natural graphite in the granules can be partially exfoliated to form an exfoliated portion.
[0021] In the method of the above aspect, in the step of kneading the slurry, at least a portion of the natural graphite in the granules can be partially exfoliated to form an exfoliated portion.
[0022] The method of the above aspect may further include the step of adding a binder and a solvent to the slurry after the step of kneading the slurry. Effect of the Invention
[0023] A granule of artificial graphite and natural graphite is used as the graphite-based material for the negative electrode active material, and some of the natural graphite in the granules is partially flaked to form flaked parts. This allows the silicon-based material and the graphite-based material to come into contact over a wide area through the flaked parts, or the silicon-based material is combined with some of the flaked parts, thereby forming a highly reliable and strong conductive path with the graphite, allowing for repeated stable charging and discharging and improving the life characteristics. [Brief description of the drawings]
[0024] [Figure 1] 1 is an SEM image of the surface of the negative electrode of Example 3. [Diagram 2] 11 is another SEM image of the negative electrode surface of Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0025] Hereinafter, an embodiment of the present invention will be described, however, the present invention is not limited to the following embodiment.
[0026] Throughout this application, unless otherwise specified, the term "average particle size" refers to the particle size at 50% of the cumulative value in the particle size distribution measured by a laser diffraction scattering method, i.e., the median diameter (D 50 In addition, the symbol "~" is used to mean both ends of the range indicated in the description. For example, "1~2" means "1 or more and 2 or less."
[0027] [Nonaqueous electrolyte secondary battery] One embodiment of the present invention relates to a non-aqueous electrolyte secondary battery. The non-aqueous electrolyte secondary battery according to this embodiment includes a negative electrode, a positive electrode, a separator interposed between the negative electrode and the positive electrode, and a non-aqueous electrolyte. A specific example of the secondary battery is a lithium ion secondary battery having advantages such as high energy density, discharge voltage, and output stability.
[0028] The following description will be given mainly by taking a lithium ion secondary battery as an example, however, the present invention is not limited to lithium ion secondary batteries and can be applied to various non-aqueous electrolyte secondary batteries.
[0029] A lithium ion secondary battery according to an embodiment of the present invention includes a negative electrode, a positive electrode, a separator interposed between the negative electrode and the positive electrode, and a non-aqueous electrolyte. The lithium ion secondary battery may also include a battery case that houses an electrode assembly including the negative electrode, the positive electrode, and the separator, and a sealing member that seals the battery case.
[0030] [Negative electrode] The negative electrode includes a negative electrode current collector and a negative electrode active material layer formed on one or both surfaces of the negative electrode current collector. The negative electrode active material layer may be formed on the entire surface of the negative electrode current collector, or may be formed only on a portion of the surface.
[0031] (Negative electrode current collector) The negative electrode current collector used in the negative electrode is not particularly limited as long as it does not induce chemical changes in the battery and has electrical conductivity. For example, the negative electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like, or an aluminum-cadmium alloy.
[0032] The negative electrode current collector may have a thickness of 3 μm or more and 500 μm or less. Fine irregularities may be formed on the surface of the negative electrode current collector to enhance adhesion to the negative electrode active material. The negative electrode current collector may have various forms, such as a film, a sheet, a foil, a net, a porous body, a foam, a nonwoven fabric, etc.
[0033] (Negative electrode active material layer) The negative electrode active material layer can be formed, for example, by applying a negative electrode slurry in which a mixture of a negative electrode active material, a binder, and a conductive material is dissolved or dispersed in a solvent to a negative electrode current collector, followed by drying and rolling, or by casting the negative electrode slurry on another support, peeling it off from the support, and laminating the resulting film on the negative electrode current collector. The mixture can further contain a dispersant, a filler, and other optional additives as necessary.
[0034] The negative electrode active material may be included in an amount of 70% by weight or more and 99% by weight or less based on the total weight of the negative electrode active material layer.
[0035] (Negative electrode active material) In the lithium ion secondary battery according to the embodiment, the negative electrode active material contains at least a graphite-based material and a silicon-based material.
[0036] Graphite-based materials include granules of artificial graphite and natural graphite. For example, the granules are granulated by adhering natural graphite particles to artificial graphite particles as a base material (core). Granulation can be performed by a known method such as a dry method in which artificial graphite and natural graphite are mixed in the air or the like and granulated by applying a mechanical / physical force, or a wet method in which artificial graphite and natural graphite are dispersed in a solvent, mixed, and then the solvent is removed.
[0037] Artificial graphite is graphite that is industrially produced by baking (i.e., graphitizing) easily graphitizable carbon materials such as coke and coal tar pitch at high temperatures (e.g., about 2800°C). For example, mesocarbon microbeads, mesocarbon fibers, massive artificial graphite, etc. are known as artificial graphite, but the artificial graphite that can be used in the present invention is not particularly limited. In general, artificial graphite is harder than natural graphite, and is known to expand less due to charge and discharge than natural graphite when used in the negative electrode of a lithium ion secondary battery.
[0038] Natural graphite is graphite produced by mining graphite ore and processing it with ore dressing, refining, etc. As natural graphite, flake-like, lump-like, earth-like, etc. are known, but the natural graphite that can be used in the present invention is not particularly limited.
[0039] The sizes of the artificial graphite and natural graphite used for the granules are selected so that the desired size of the granules formed by granulating them is obtained. The average particle size (D 50 ) may be, for example, 3 μm or more and 30 μm or less, preferably 5 μm or more and 25 μm or less, more preferably 15 μm or more and 20 μm or less, and may be 20 μm as an example.
[0040] The weight ratio of the artificial graphite to the natural graphite in the granules is selected so that a sufficient amount of natural graphite is present, particularly on the surface of the granules, and can be, for example, (artificial graphite:natural graphite) = 60:40 to 90:10, and as an example, can be 80:20.
[0041] Examples of silicon-based materials include silicon oxide, silicon-based alloys, silicon (Si) powder, silicon nanoparticles, silicon nanowires, etc., and these can be used alone or as a mixture of two or more. Preferably, either one or both of silicon oxide and silicon-based alloys can be used.
[0042] Silicon oxide is represented by the general formula SiO x where x satisfies 0 < x < 2, and for example, it can be SiO (x = 1). Silicon oxide can have a structure in which Si fine particles are dispersed in an amorphous silicon oxide matrix in the form of microcrystals or amorphous. Silicon oxide may contain only SiO x with a specific value of x, or it may be a mixture of two or more SiO x with different values of x.
[0043] The silicon-based alloy can be a granule having a particle structure in which fine particles of transition metal silicide are dispersed in an amorphous silicon matrix in the form of microcrystals or amorphous. Such granules of silicon-based alloy can be obtained, for example, by atomizing a silicon alloy powder by atomization treatment (preferably gas atomization treatment) of silicon and a transition metal, and then amorphizing silicon by mechanical alloying treatment. The content of amorphous silicon in the granules of the above silicon-based alloy can be, for example, 10 wt% or more and 60 wt% or less, preferably 20 wt% or more and 40 wt% or less. The transition metal of the silicide can be one or more of titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), and copper (Cu). As a combination of two or more transition metals, for example, Cr, Ti, and Fe are selected, and preferably Cr and Ti are selected. When Cr and Ti are used, SiCrTi alloy powder is obtained, and the silicides in the powder include binary silicides such as CrSi, CrSi2, TiSi2, TiSi, etc., Cr x Si y Ti zTheoretically, a ternary silicide of the above is formed. In the case of SiCrTi alloy powder, the main component may be Si at 70 atomic % or more and 90 atomic % or less, and the remainder may be transition metal components. For example, the atomic ratio of Si, Cr, and Ti (Si:Cr:Ti) may be 84 atomic %: 8 atomic %: 8 atomic %, or 82.4 atomic %: 8.8 atomic %: 8.8 atomic %, etc.
[0044] The silicon-based material may be in particulate form, and the average particle size of the silicon-based material particles (D 50 ) can be, for example, 0.1 μm to 10 μm, in particular 1 μm to 5 μm, for example 5 μm, or 1 μm to 2 μm.
[0045] The average particle size of the silicon-based material particles can be selected to be smaller than the average particle size of the graphite-based material particles. In this way, by making the silicon-based material particles smaller, the silicon-based material having a higher expansion coefficient than the carbon-based material can be placed in the voids in the negative electrode (for example, the voids between the carbon-based materials) or on the surface or inside the carbon-based material.
[0046] The weight ratio of the graphite-based material to the silicon-based material in the negative electrode active material can be selected in consideration of the expansion coefficient and capacity of the silicon-based material, and can be, for example, the weight ratio of the graphite-based material to the silicon-based material (graphite-based material:silicon-based material) = 98:2 to 50:50, particularly 98:2 to 70:30, and can be, for example, 90:10.
[0047] (binder) The binder is added as a component that promotes the bonding between the active material and the conductive material, the bonding with the current collector, etc. Examples of binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), polyacrylic acid, acrylamide, polyimide, fluororubber, various copolymers thereof, and the like, and one or a mixture of two or more of these may be used, but the binder is not limited to these.
[0048] The content of the binder may be 0.1% by weight or more and 30% by weight or less based on the total weight of the negative electrode active material layer. The content of the binder may be preferably 0.5% by weight or more and 20% by weight or less, and more preferably 1% by weight or more and 10% by weight or less. When the content of the binder polymer satisfies the above range, it is possible to provide sufficient adhesive strength within the electrode while preventing a decrease in the capacity characteristics of the battery.
[0049] (Conductive material) The conductive material is not particularly limited as long as it is an electrically conductive material that does not induce chemical changes. Examples of the conductive material include carbon-based materials such as artificial graphite, natural graphite, carbon nanotubes, graphene, carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, lamp black, and carbon fibers (carbon-based materials added separately from the carbon-based material as the negative electrode active material); metal powders and metal fibers such as aluminum, tin, bismuth, silicon, antimony, nickel, copper, titanium, vanadium, chromium, manganese, iron, cobalt, zinc, molybdenum, tungsten, silver, gold, lanthanum, ruthenium, platinum, and iridium; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive polymers such as polyaniline, polythiophene, polyacetylene, polypyrrole, and polyphenylene derivatives, and the like, and a mixture of one or more of these may be used, but are not limited thereto.
[0050] Advantageously, from the viewpoints of dispersibility and cost, the conductive material of the carbon-based material may be selected as the conductive material, such as carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, lamp black, and in particular carbon black, but this does not exclude the use of artificial graphite, natural graphite, carbon nanotubes, and graphene as the conductive material.
[0051] The content of the conductive material may be 0.1% by weight or more and 30% by weight or less based on the total weight of the negative electrode active material layer. The content of the conductive material may be preferably 0.5% by weight or more and 15% by weight or less, more preferably 0.5% by weight or more and 10% by weight or less. When the content of the conductive material satisfies the above range, it is advantageous in that sufficient conductivity can be imparted and the amount of the negative electrode active material is not reduced, thereby ensuring the battery capacity.
[0052] (Thickener) The negative electrode slurry may further include a thickener. Specifically, the thickener may be a cellulose-based compound. Examples of the cellulose-based compound include carboxymethyl cellulose (CMC), methyl cellulose (MC), hydroxypropyl cellulose (HPC), methyl hydroxypropyl cellulose (MHPC), ethyl hydroxyethyl cellulose (EHEC), methyl ethyl hydroxyethyl cellulose (MEHEC), and the like, and any one or a combination of two or more of these may be used. The thickener may be included in an amount of, for example, 0.5% by weight to 10% by weight based on the total weight of the negative electrode active material layer.
[0053] (solvent) The solvent used in the negative electrode slurry is not particularly limited as long as it is one generally used in the manufacture of negative electrodes. Examples of the solvent include pure water, N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), isopropyl alcohol, acetone, etc., and one or a mixture of two or more of these may be used, but are not limited thereto.
[0054] [Method of manufacturing the negative electrode] A method for producing a negative electrode for a lithium ion secondary battery according to an embodiment may include the steps of: (1) preparing a negative electrode slurry; (2) kneading the negative electrode slurry; and (3) producing a negative electrode from the negative electrode slurry.
[0055] (1) Step of preparing a negative electrode slurry A graphite-based material (granules of artificial graphite and natural graphite) as the negative electrode active material, a silicon-based material, a conductive material, a thickener, a binder, and a solvent are prepared. If necessary, a dispersant, a filler, and other optional additives are prepared. The thickener is easy to use if it is dissolved in a solvent (water, NMP, etc.) in advance. These materials are then mixed to prepare a slurry for the negative electrode. Specifically, first, the conductive material, the thickener, the dispersant, etc. are mixed with a solvent, and then the silicon-based material and the graphite-based material are added. When a binder is used without a thickener, part of the binder is added instead of the thickener.
[0056] The solid content in the negative electrode slurry is adjusted to be 60% by weight or more based on the weight of the entire slurry. This adjustment can be performed by adjusting the amount of solvent added to the slurry. Preferably, the solid content in the negative electrode slurry is adjusted to be 65% by weight or more. If the solid content is less than 60% by weight, the viscosity of the slurry is low, so that sufficient shear stress cannot be obtained in the subsequent kneading step, and in particular, the interaction (collision, impact, friction, etc.) between the graphite-based material and the silicon-based material becomes insufficient. The upper limit of the solid content in the slurry is not particularly limited as long as the subsequent kneading step is appropriately performed, but if the solid content is too high, the dispersibility of each material in the slurry decreases, so it can be set to, for example, 75% by weight or less, preferably 70% by weight or less.
[0057] (2) Step of kneading the negative electrode slurry Next, the negative electrode slurry prepared in (1) is subjected to hard mixing (also called kneading). Hard mixing can be performed by a known method such as using a planetary centrifugal mixer.
[0058] During the kneading, the solid content in the slurry is as high as 60% by weight or more, so that the silicon-based material collides violently with the graphite-based material. Here, natural graphite is generally softer than artificial graphite and silicon-based materials. Therefore, for at least a part of the natural graphite present in the granules of the graphite-based material, the surface of the natural graphite is partially exfoliated to form an exfoliated portion by the collision of the hard silicon-based material with the surface. Here, in the present application, the partial exfoliation means that the surface of the natural graphite is not completely peeled off or detached from the natural graphite, but is partially peeled off, turned over, and exfoliated, in other words, in a burr state. The exfoliated portion may be a single layer of graphene, and in this case, the exfoliation means graphene formation. Alternatively, the flaked portion may have two or more graphene layers, up to about several tens, hundreds, or thousands of layers, and may have a thickness of a few nm or less, up to a few tens of nm, or on the submicron level (e.g., about 300 nm or less, or about 100 nm or less).
[0059] On the other hand, the artificial graphite in the granules is not particularly broken during kneading due to its hardness. As a result, the graphite-based material granules as a whole can be prevented from being broken or pulverized more than necessary during kneading due to the presence of artificial graphite as the base material. Similarly, the silicon-based material, which is hard, is not particularly broken during kneading.
[0060] As the kneading process progresses, the silicon-based material disperses in the slurry, comes into contact with the granules, in particular with the flaked portions formed in the natural graphite, and can further be composited (e.g., physically and / or chemically adsorbed / bonded) with the flaked portions of the natural graphite due to the shear forces and collision forces applied during the kneading process.
[0061] During the kneading process, the temperature of the slurry can be increased to a certain degree (for example, 60°C or higher and 80°C or lower, preferably 65°C or higher and 75°C or lower), thereby promoting the kneading process and, as a result, promoting the partial flake formation of some of the natural graphite in the granules.
[0062] (3) Producing a negative electrode from the negative electrode slurry After the kneading is completed, the entire amount of binder is added, the solid content is adjusted to about 50% by weight with a solvent, and further mixed. Finally, the solid content is adjusted to an easy-to-apply concentration with a solvent, and lightly mixed. The negative electrode slurry thus produced is applied to a negative electrode current collector, and then dried and rolled to produce a negative electrode having a negative electrode active material layer formed on the negative electrode current collector. Before applying the negative electrode slurry, a solvent may be further added to the kneaded slurry to facilitate application, and then the application may be performed.
[0063] As another method, for example, the negative electrode may be produced by casting the above-mentioned negative electrode slurry on another support, peeling it off from the support, and laminating the resulting film on the negative electrode current collector. Also, the negative electrode active material layer may be formed on the negative electrode current collector by any other method.
[0064] The negative electrode obtained as described above contains at least a graphite-based material (granules of artificial graphite and natural graphite) and a silicon-based material as negative electrode active materials, and a conductive material. In at least a part of the natural graphite in the granules, the surface part is partially flaked to form a flaked portion. The flaked portion is not detached from the natural graphite, so it is present in various directions on the surface of the granules, contacts adjacent silicon-based materials and other granules, and further, some of the flaked portions are composited with the silicon-based material to establish an isotropic conductive path in the negative electrode. The conductive path formed by the flaked portion originates from the granules as the negative electrode active material, so there is no problem with dispersion. In addition, a conductive material is added, so that the conductive path is further improved. In addition, the silicon-based material having a small particle size is in contact with the granules over a wide area through the flaked portion, or is composited with the flaked portion, so that the conductive path is formed highly and firmly throughout the entire negative electrode.
[0065] [Positive electrode] In the lithium ion secondary battery according to the embodiment, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on one or both surfaces of the positive electrode current collector. The positive electrode active material layer may be formed on the entire surface of the positive electrode current collector, or may be formed only on a portion of the surface.
[0066] (Positive electrode current collector) The positive electrode current collector used in the positive electrode is not particularly limited as long as it does not induce chemical changes in the battery and has electrical conductivity.For example, as the positive electrode current collector, stainless steel; aluminum; nickel; titanium; baked carbon; aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used.
[0067] The positive electrode current collector may have a thickness of 3 μm or more and 500 μm or less. Fine irregularities may be formed on the surface of the positive electrode current collector to enhance adhesion to the positive electrode active material. The positive electrode current collector may have various forms, such as a film, a sheet, a foil, a net, a porous body, a foam, a nonwoven fabric, etc.
[0068] (Cathode active material layer) The positive electrode active material layer can be formed, for example, by applying a positive electrode slurry, in which a mixture of a positive electrode active material, a conductive material, and a binder is dissolved and dispersed in a solvent, to a positive electrode current collector, followed by drying and rolling. The mixture can further contain a thickener, a dispersant, a filler, and other optional additives, as necessary.
[0069] The positive electrode active material may be contained in an amount of 80% by weight or more and 99% by weight or less based on the total weight of the positive electrode active material layer.
[0070] (Cathode active material) As the positive electrode active material, a compound capable of reversible insertion (intercalation) and desorption (deintercalation) of lithium can be used. Specific examples include, for example, lithium metal composite oxides containing one or more metals such as cobalt, manganese, nickel, copper, vanadium, and aluminum and lithium. More specifically, such lithium metal composite oxides include lithium-manganese-based oxides (for example, LiMnO2, LiMnO3, LiMn2O3, LiMn2O4, etc.); lithium-cobalt-based oxides (for example, LiCoO2, etc.); lithium-nickel-based oxides (for example, LiNiO2, etc.); lithium-copper-based oxides (for example, Li2CuO2, etc.); lithium-vanadium-based oxides (for example, LiV3O8, etc.); lithium-nickel-manganese-based oxides (for example, LiNi 1-z Mn z O2(0 < z < 1), LiMn 2-z Ni z O4(0 < z < 2), etc.); lithium-nickel-cobalt-based oxides (for example, LiNi 1-y Co y O2(0 < y < 1), etc.); lithium-manganese-cobalt-based oxides (for example, LiCo 1-z Mn z O2(0 < z < 1), LiMn 2-y Co y O4(0 < y < 2), etc.); lithium-nickel-manganese-cobalt-based oxides (for example, Li(Ni x Co y Mn z )O2(0 < x < 1, 0 < y < 1, 0 < z < 1, x + y + z = 1), Li(Ni x Co y Mn z )O4(0 < x < 2, 0 < y < 2, 0 < z < 2, x + y + z = 2), etc.); lithium-nickel-cobalt-metal (M) oxides (for example, Li(Ni x Co y Mn z M w)O2 (M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, 0 < x < 1, 0 < y < 1, 0 < z < 1, 0 < w < 1, x + y + z + w = 1), etc.); Examples include compounds in which the transition metal elements in these compounds are partially substituted with one or more other metal elements. The positive electrode active material layer can contain any one or two or more of these compounds. However, it is not limited to these only.
[0071] In particular, in terms of improving the capacity characteristics and stability of the battery, LiCoO2, LiMnO2, LiMn2O4, LiNiO2, lithium nickel manganese cobalt oxide (for example, Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.4 Mn 0.3 Co 0.3 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.), lithium nickel cobalt aluminum oxide (for example, Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.) are preferred.
[0072] (Binder and conductive material) The types and contents of the binder and conductive material used in the positive electrode slurry can be the same as those described for the negative electrode.
[0073] (Solvent) The solvent used in the positive electrode slurry is not particularly limited as long as it is generally used in the manufacture of a positive electrode. Examples of the solvent include pure water, amine solvents such as N,N-dimethylaminopropylamine, diethylenetriamine, and N,N-dimethylformamide (DMF), ether solvents such as tetrahydrofuran, ketone solvents such as methyl ethyl ketone, ester solvents such as methyl acetate, amide solvents such as dimethylacetamide and 1-methyl-2-pyrrolidone (NMP), and dimethylsulfoxide (DMSO), and one or a mixture of two or more of these may be used, but are not limited thereto.
[0074] The amount of the solvent used is sufficient as long as it is capable of dissolving or dispersing the positive electrode active material, conductive material, and binder and has a viscosity that allows excellent thickness uniformity to be exhibited when applied to the positive electrode current collector, taking into consideration the coating thickness of the slurry and the production yield.
[0075] [Cathode manufacturing method] A manufacturing method of a positive electrode for a lithium ion secondary battery according to the embodiment may include a step of obtaining a positive electrode slurry by dissolving or dispersing a positive electrode active material, together with a binder, a conductive material, a thickener, and the like as necessary, in a solvent, and a step of obtaining a positive electrode by forming a positive electrode active material layer on a positive electrode current collector, for example by applying the positive electrode slurry onto the positive electrode current collector, in a manner similar to the manufacturing method of a negative electrode.
[0076] [Separator] In the lithium ion secondary battery according to the embodiment, the separator separates the negative electrode and the positive electrode to provide a path for lithium ions to move, and any separator that is generally used as a separator in a lithium ion secondary battery can be used without any particular limitation. In particular, a separator that has a small resistance to ion movement of the electrolyte and has an excellent moisture-absorbing ability of the electrolyte is preferable. For example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, or a laminated structure of two or more layers thereof, can be used as the separator. In addition, a normal porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber or polyethylene terephthalate fiber, can also be used. In addition, a separator coated with a ceramic component or a polymeric substance to ensure heat resistance or mechanical strength may be used.
[0077] [Non-aqueous electrolyte] In the non-aqueous electrolyte secondary battery according to this embodiment, examples of the non-aqueous electrolyte include organic liquid electrolytes and inorganic liquid electrolytes that can be used in the manufacture of secondary batteries, but are not limited thereto.
[0078] The non-aqueous electrolyte may contain an organic solvent and a lithium salt, and may further contain additives as necessary. Hereinafter, the liquid electrolyte may also be referred to as an "electrolytic solution."
[0079] The organic solvent may be used without particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Examples of organic solvents include ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether solvents such as dibutyl ether and tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC); alcohol solvents such as ethyl alcohol and isopropyl alcohol; nitrile solvents such as R-CN (R is a C2 to C20 linear, branched, or cyclic hydrocarbon group that may contain a double bond aromatic ring or an ether bond); amide solvents such as dimethylformamide; dioxolane solvents such as 1,3-dioxolane; and sulfolane solvents. One or a mixture of two or more of these may be used, but the present invention is not limited to these. In particular, carbonate-based solvents are preferred, and mixtures of cyclic carbonates (e.g., ethylene carbonate, propylene carbonate, etc.) having high ionic conductivity and high dielectric constant capable of enhancing the charge / discharge performance of batteries and low-viscosity linear carbonate-based compounds (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, etc.) are more preferred. In this case, when the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to 1:9, excellent electrolyte performance can be exhibited.
[0080] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium ion secondary battery. Examples of the lithium salt include LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2, and one or a mixture of two or more of these can be used, but are not limited thereto. The lithium salt can be contained in the electrolyte at a concentration of, for example, 0.1 mol / L or more and 2 mol / L or less. When the concentration of the lithium salt is within this range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.
[0081] Additives can be used as necessary for the purpose of improving battery life characteristics, suppressing the decrease in battery capacity, and improving battery discharge capacity. Examples of additives include haloalkylene carbonate compounds such as fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride, and one or a mixture of two or more of these can be used, but are not limited to these. The additives can be contained in an amount of, for example, 0.1% by weight to 15% by weight based on the total weight of the electrolyte.
[0082] In particular, fluoroethylene carbonate and difluoroethylene carbonate can act as a film-forming agent that forms a film at the interface between the electrode and the electrolyte. For example, when at least one of fluoroethylene carbonate and difluoroethylene carbonate is included, a good SEI film is formed in the process of alloying the silicon-based material and lithium in the negative electrode using the negative electrode active material containing the silicon-based material, so that stable charging and discharging can be performed. The content of the film-forming agent can be, for example, 0.1% by weight or more and 15% by weight or less, preferably 0.5% by weight or more and 10% by weight or less, and more preferably 1% by weight or more and 7% by weight or less, based on the total weight of the electrolyte. The film-forming agent can include at least one of fluoroethylene carbonate and difluoroethylene carbonate.
[0083] [Method of manufacturing non-aqueous electrolyte secondary battery] The nonaqueous electrolyte secondary battery according to the embodiment may be manufactured by interposing a separator (e.g., a separator membrane) and an electrolyte between the negative electrode manufactured as described above and the positive electrode manufactured as described above. More specifically, a separator is disposed between the negative electrode and the positive electrode to form an electrode assembly, and the electrode assembly is placed in a battery case such as a cylindrical battery case or a prismatic battery case, and then an electrolyte is injected to manufacture the nonaqueous electrolyte secondary battery. Alternatively, the electrode assemblies may be stacked, and the resulting product obtained by impregnating the electrode assemblies with an electrolyte is placed in a battery case and sealed to manufacture the battery.
[0084] The battery case may be one commonly used in the art, and may have, for example, a cylindrical shape using a can, a rectangular shape, a pouch shape, or a coin shape.
[0085] The lithium ion secondary battery according to the embodiment can be used not only as a power source for a small device, but also as a unit battery of a medium- to large-sized battery module including a large number of battery cells, etc. Preferred examples of such medium- to large-sized devices include, but are not limited to, electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0086] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0087] [Example 1] 90% by weight of granules of artificial graphite and natural graphite (average particle size 20μm, weight ratio of artificial graphite to natural graphite = 8:2) and 10% by weight of silicon monoxide (SiO) with an average particle size of 5μm were mixed, and 1% by weight of carbon black as a conductive material and 1.7% by weight of carboxymethylcellulose (CMC) as a thickener were added to this mixture, and pure water was added to adjust the solid content to 65% by weight to prepare a slurry, which was then kneaded with a planetary stirrer. The temperature of the slurry during kneading was 70°C. 1.5% by weight of styrene butadiene rubber (SBR) was added as a binder to the obtained slurry, and pure water was added to adjust the solid content to 50% by weight for ease of application, after which the slurry was applied to copper foil, dried at 60°C for 30 minutes, and then vacuum dried at 120°C for 12 hours, followed by rolling to produce a negative electrode with an electrode density of 1.65g / cc.
[0088] [Example 2] A negative electrode was produced in the same manner as in Example 1, except that the amount of pure water was adjusted so that the solid content of the slurry during kneading was 60% by weight. The temperature of the slurry during kneading was 65°C.
[0089] [Example 3] A negative electrode was produced in the same manner as in Example 1, except that SiCrTi alloy granules having an average particle size of 2 μm (atomic weight ratio of Si, Cr, and Ti (Si:Cr:Ti)=82.4:8.8:8.8) were used instead of silicon monoxide (SiO) mixed with the granules of artificial graphite and natural graphite. The temperature of the slurry during the kneading was 72° C.
[0090] [Comparative Example 1] Except for adjusting the amount of pure water so that the solid content of the slurry during kneading was 55% by weight, a negative electrode was produced in the same manner as in Example 1. The temperature of the slurry during kneading was 57°C.
[0091] [Comparative Example 2] A negative electrode was produced in the same manner as in Example 3, except that the amount of pure water was adjusted so that the solid content of the slurry during kneading was 55% by weight. The temperature of the slurry during kneading was 58°C.
[0092] [Comparative Example 3] Except for using artificial graphite powder having an average particle size of 20 μm instead of the granules of artificial graphite and natural graphite, a negative electrode was produced in the same manner as in Example 1. The temperature of the slurry during kneading was 36° C.
[0093] [Comparative Example 4] A negative electrode was produced in the same manner as in Example 1, except that instead of the granules of artificial graphite and natural graphite, a powder mixture in which artificial graphite powder having an average particle size of 20 μm and natural graphite powder having an average particle size of 5 μm were mixed in a weight ratio of 8 to 2 was used. The temperature of the slurry during the kneading was 50° C.
[0094] [Comparative Example 5] Except for using 1 wt % graphene as the conductive material instead of 1 wt % carbon black, a negative electrode was produced in the same manner as in Comparative Example 3. The temperature of the slurry during kneading was 36°C.
[0095] [Comparative Example 6] Except for using natural graphite powder having an average particle size of 20 μm instead of the granules of artificial graphite and natural graphite, a negative electrode was produced in the same manner as in Comparative Example 1. The temperature of the slurry during kneading was 57° C.
[0096] [Evaluation example 1: SEM observation] The negative electrode prepared in Example 3 was observed using a scanning electron microscope (SEM). SEM images showing the natural graphite portion in the negative electrode are shown in Figs. 1 and 2. As shown in these SEM images, the surface of the natural graphite is partially flaked and in a jagged state. In particular, in the SEM image of Fig. 2, it can be seen that the surface of the natural graphite is partially turned over and graphene is formed, and that Si alloy granules are dispersed and in contact with the surface of the flaked portion.
[0097] [Evaluation Example 2: Capacity Retention Rate] The capacity retention rate was evaluated as the life characteristic as follows. For each negative electrode prepared in Examples 1 to 3 and Comparative Examples 1 to 6, metallic lithium was used as a counter electrode (i.e., a positive electrode), and a coin battery (half cell) was manufactured. Then, for each coin battery, the first cycle (initial) of charge and discharge was performed at a constant current of 0.2C with a cutoff voltage of 1.5V. After the second cycle (second time) of charge and discharge was performed under the same conditions, the same charge and discharge was repeated 48 cycles (48 times) at a constant current of 0.5C, and the discharge capacity (mAh) was measured. That is, a total of 50 charge and discharge processes were repeated, including the first and second charge and discharge processes. The capacity retention rate was defined and obtained as the ratio of the discharge capacity in the 50th cycle of the charge and discharge process to the discharge capacity in the 3rd cycle of the charge and discharge process (discharge capacity in the 50th cycle / discharge capacity in the 3rd cycle). The results are shown in Table 1 below.
[0098] [Table 1]
[0099] As is clear from Table 1 above, in Examples 1 to 3, in which artificial graphite and natural graphite granules were used as graphite-based materials and the content of the slurry solids during kneading was 60% by weight or more, a good capacity retention rate was obtained. This is believed to be because a high-level and strong conductive path was established throughout the negative electrode due to partial flaking of the natural graphite, and the conductive path was maintained even if the negative electrode active material (especially the silicon-based material) repeatedly expanded during charging and discharging. In addition, in Examples 1 to 3, the slurry temperature during kneading was relatively high at 65°C or more, which is believed to have promoted the kneading process.
[0100] On the other hand, as shown in Comparative Examples 1 and 2, even when granules of artificial graphite and natural graphite are used as the graphite-based material, when the content of the slurry solids during kneading is low at 55% by weight, the capacity retention rate is low. This is thought to be because the viscosity of the slurry during kneading is low and the natural graphite in the granules does not flake. Similarly, in Comparative Example 6, it is thought that the natural graphite powder is not particularly flaked.
[0101] The low capacity retention rates in Comparative Example 3 and Comparative Example 5 are believed to be due to the fact that the artificial graphite is harder than natural graphite, so that the artificial graphite does not flake during kneading, and therefore a high-level and strong conductive path is not established as in Examples 1 to 3. In addition, with regard to Comparative Example 5, it is difficult to bring graphene into contact with both the graphite-based material and the silicon-based material by simply adding graphene, and it is not easy to uniformly disperse it in the negative electrode. Furthermore, since graphene tends to be oriented parallel to the current collector, an isotropic conductive path is not ensured as in Examples 1 to 3, and it is believed that the conductive path perpendicular to the surface of the current collector is particularly insufficient.
[0102] In Comparative Example 4, a mixture of artificial graphite and natural graphite is simply used, and therefore the artificial graphite is not flaked during kneading, while the soft natural graphite is pulverized excessively. This is thought to result in a lower capacity retention rate compared to Examples 1 to 3, in which the presence of artificial graphite as a base material suppresses excessive pulverization of the natural graphite.
Claims
1. A negative electrode for a secondary battery, The negative electrode comprises at least a graphite-based material and a silicon-based material as a negative electrode active material, and a conductive material; The graphite-based material includes granules of artificial graphite and natural graphite, At least a part of the natural graphite in the granules is partially grapheneized to form a graphene portion having a thickness of 300 nm or less; The graphenized portion is in contact with the silicon-based material or other artificial graphite and natural graphite granules, or is composited with the silicon-based material.
2. The anode of claim 1 , wherein the silicon-based material comprises one or both of silicon oxide and silicon-based alloy.
3. 3. The negative electrode according to claim 2, wherein the silicon-based alloy contains one or more of titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni) and copper (Cu).
4. The negative electrode according to claim 1 , wherein the conductive material is carbon black.
5. 5. The negative electrode according to claim 1, wherein a weight ratio of the graphite-based material to the silicon-based material is 98:2 to 50:
50.
6. 6. The negative electrode according to claim 1, wherein a weight ratio of artificial graphite to natural graphite in the granules is from 60:40 to 90:
10.
7. A secondary battery comprising: the negative electrode according to claim 1 ; a positive electrode; a separator interposed between the negative electrode and the positive electrode; and an electrolyte.
8. A slurry for a negative electrode of a secondary battery, The slurry contains a graphite-based material and a silicon-based material as negative electrode active materials, a conductive material, a solvent, and at least one of a thickener and a binder, so that the solid content in the slurry is 60% by weight or more; The graphite-based material includes granules of artificial graphite and natural graphite, The slurry for a negative electrode, wherein at least a part of the natural graphite in the granules is partially converted into graphene to form a graphene portion with a thickness of 300 nm or less.
9. 9. The negative electrode slurry according to claim 8, wherein the slurry has a solid content of 65% by weight or more and 75% by weight or less.
10. A method for producing a negative electrode for a secondary battery, comprising the steps of: A step of mixing a graphite-based material and a silicon-based material as negative electrode active materials, a conductive material, a solvent, and at least one of a thickener and a binder to prepare a slurry having a solid content of 60 wt % or more; kneading the slurry; and applying the slurry to a current collector to produce a negative electrode. The graphite-based material is a granule of artificial graphite and natural graphite, The method, wherein, in the step of kneading the slurry, at least a portion of the natural graphite in the granules is partially grapheneized to form a graphene portion having a thickness of 300 nm or less.
11. The method of claim 10, further comprising the step of adding further binders and solvents to the slurry after the step of kneading the slurry.
Citation Information
Patent Citations
Non-aqueous electrolyte secondary battery
JP2004146292A
Anode active substance for lithium ion secondary battery
JP2008027897A
Negative electrode active material for lithium secondary battery, negative electrode using the same, and manufacturing method
JP2008186732A
Anode material for nonaqueous secondary battery, anode for nonaqueous secondary battery, and nonaqueous secondary battery
JP2018088406A
Negative electrode active material and negative electrode containing the same
JP2018514918A
